Peran Pesantren dalam Pembentukan Karakter Religius di Kalangan Remaja Milenial (Studi Konseptual di Pondok Pesantren Sunan Drajat Lamongan) - Wanto Wanto (LPPM Ma'had Aly Sunan Drajat Lamongan, 2025)
The development of digital technology and the influence of global culture have significantly affected the formation of the religious character of millennial youth, as reflected in the shifting values of spirituality and morality. In this context, Islamic boarding schools (pesantren) as traditional Islamic educational institutions hold a strategic role in preserving and instilling strong religious values amid the currents of modernization. This study aims to analyze the role of pesantren in shaping the religious character of millennial youth, focusing on the educational system and character-building practices at Pondok Pesantren Sunan Drajat Lamongan. This research employs a descriptive qualitative method with a conceptual study approach through literature reviews and analysis of educational concepts relevant to religious character formation in the digital era. The findings indicate that pesantren play a central role in the internalization of religious values through the habituation of worship, the exemplary conduct of kiai (religious leaders), and a disciplined, spiritual environment. However, challenges arise from the influence of social media and global culture, which often conflict with Islamic values. The results of this study demonstrate that pesantren remain a moral and spiritual fortress for the millennial generation. The constructive use of digital media is an essential strategy to strengthen the effectiveness of religious character development amid the challenges of the digital era.